The geology of Mount Orliakas and the Pindos Ophiolite, Greece. - Wong, Kevin; Draper, Kathryn; Feng, Linshu; Hawkins, Philip; Oakley, Samuel; Zheng, Xiao Xu (Bulletin of the Geological Society of Greece, 2019)
The Greveniotiki Pindos Mountains of Greece showcases the tectonics aﬀecting the Central Mediterranean; however no detailed geological maps have been produced of the region. In this study we present a 1:10000 geological map of Mount Orliakas and its surrounding areas, including westernmost parts of the Pindos Ophiolite complex and the Mesohellenic basin. We also provide new lithological, structural, and palaeontological discussions of the region and give new evidence for the provenance of the Kranea Formation.